INNOVATIVE AREAS OF EDUCATIONAL DEVELOPMENT IN ACHIEVING PROGRESS - A. Tadjibaeva (Academia Science Repository, 2023)
The article scientifically investigated the content of education and the innovative directions of its development, as well as the importance of innovative technologies in the field of Education.